Pelatihan Pembuatan Bahan Ajar Untuk Pembelajaran Matematika Pada Guru SD Negeri Krueng Baung - Nurdiana Nurdiana; Patri Janson Silaban; Lasma Silaban (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
One concrete element that is very important in efforts to improve the quality of human resources is improving the quality of education. However, in reality, teachers do not develop the creativity to plan, prepare and create mature teaching materials that are rich in innovation so that they are attractive to students. Problems regarding teachers' lack of awareness of the importance of preparing teaching materials that suit their needs, the benefits of teaching materials in preparing learning tools and implementing learning. The community service carried out is based on the aim of improving the ability of teachers at Krueng Baung State Elementary School in compiling and developing teaching materials. This activity was carried out by students from the Elementary School Teacher Education study program. The results of the preparation and production of teaching materials show that all participants understand what teaching materials are and have succeeded in compiling teaching materials according to the preparation process. The results of the teaching materials obtained are in the form of LKPD and Modules. Apart from that, based on the results of the interviews, all participants expressed positive responses to the training activities presented by the presenters. However, the obstacle faced is that teachers have difficulty understanding how to compile student competency indicators in the teaching materials they will create. One of the recommendations and shared commitments from teachers is to always train themselves in their ability to prepare good teaching materials.